An insight into the holistic Islamic management: a comprehensive analysis - Abdullah @ Chuah Hock Leng, Osman (s.n, 2012)
Good management is very essential for any business organization. Management is a difficult science as it deals with the planning and organizations of the various factors of production including the human behaviors. It is also not easy to set up and institutionalized good management system in the big organizations. The purpose of this paper is to develop a conceptual framework of Islamic management based on Islam.